PENGARUH MAJALAH PEMERIKSA TERHADAP PENGETAHUAN AUDITOR - Kusuma, Tiara Ayu (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Research Investigator Magazine, which is expected to occur increasing knowledge about Rebublik Indonesian Supreme Audit Agency (BPK-RI) and enhancing the performance of auditors to further advance Rebublik IndonesianSupreme Audit Agency (BPK-RI). This paper, the author would like to see âHow to Influence Magazine Coroner Auditor Knowledge Against Rebublik Indonesian Audit Boardâ. Expected Magazine Audit Audit Board of the Republic of Indonesia, including in both categories, and knowledge Auditor Audit Board of Indonesia is also expected either. In addition to the influence of knowledge Auditor Investigator magazine BPK RI expected strong. This research is explanatory and is correlational, the time the study was conducted in September 2009 to March2010, the study population were employees BPK auditor Rebublik Indonesia.The study authors used sampling techniques Probability Proportionate Stratified Random Sampling and Sampling, data collection by questionnaire and literature, the authors also use a Likert scale to measure attitudes, opinions and perceptions of employees and which can be translated into measurable components.Â